Comparison of Personal Data Protection Laws Indonesia and Thailand - yuspin, wardah; Tampawestri, Miranti Kusretno; Jati, Ridho Bawana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The era of globalization puts information technology in an important position because it can create a part of the world without any restrictions, distance, space, and time and can increase work productivity and time efficiency. The importance of personal data protection has become stronger by increasing number of cell phone and internet users. The emergence the leakage of personal data realizes the protection of personal data is very important because it involves the concept of one’s privacy. This research uses juridical-normative approach method by examining and analyzing legal aspects and comparing laws and using descriptive research type. This research aims to examine at Indonesian and Thai laws protecting personal data in providing sanctions for personal data violators and personal data supervisors. Indonesia has not officially had a personal data protection supervisory body in the PDP Law has not regulated a special supervisory body for personal data protection. In Thailand’s PDPA, the supervisory body is clearly regulated. Sanctions for violators of personal data protection in the PDP Law and PDPA both have criminal and administrative.